C-reactive protein serum level in patients with psoriasis before and after treatment with narrow-band ultraviolet B - Mahmoud Farshchian; Akram Ansar; Mohammadreza Sobhan; Valiollah Hoseinpoor (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Background: C-reactive protein is an inflammatory biomarker and its level increases in the serum of psoriatic patients. Its level is also associated with Psoriasis Area and Severity Index score. Objective: The aim of this study was to assess the decrement of serum C-reactive protein level with narrow-band ultraviolet B (NB-UVB) therapy. Methods: C-reactive protein serum levels in psoriasis patients were measured before and after treatment with NB-UVB and the data were analyzed in relation to the Psoriasis Area and Severity Index score improvement. Results: Baseline C-reactive protein levels among psoriatic patients were higher than normal. These levels decreased significantly after treatment (P<0.001). At the beginning of the study, patients with higher levels of C-reactive protein also had more extensive and severe skin involvement. The highest decrease in C-reactive protein was observed in patients who responded better to the treatment and achieved a higher Psoriasis Area and Severity Index 75%. There was an association between baseline Psoriasis Area and Severity Index scores and C-reactive protein levels. Conclusion: Patients with moderate to severe plaque-type psoriasis had active systemic inflammation, which was demonstrated by increased levels of C-reactive protein. Furthermore, skin disease severity was correlated with C-reactive protein levels. Phototherapy healed the psoriatic skin lesions and reduced inflammation, while decreasing C-reactive protein levels.